Molecular profiling of CNS tumors for the treatment and management of disease. (January 2020) - Nie, Qian; Hsiao, Meng-Chang; Chandok, Harshpreet; Rowe, Shannon; Prego, Matthew; Meyers, Bridgette; Omerza, Gregory; Hesse, Andrew; Uvalic, Jasmina; Soucy, Melissa; Bergeron, Daniel; Peracchio, Michael; et al.
Highlights: This retrospective study evaluates the molecular profiles in 48 glioblastoma in comparison to TCGA and MSK data sets. Hundred and thirty-one clinically significant variants were identified across 30 of the 212 genes evaluated (14%). CDK4/6 and PI3K inhibitors were the most commonly reported drug class with FDA approved and investigational therapies. Abstract: The World Health Organization (WHO) has defined more than 130 distinct central nervous system (CNS) tumor entities, of which glioblastoma is the most fatal primary brain tumor. However, the correlation of the molecular signatures of glioblastoma with clinical significance for precision medicine is not well-known. How, and to what extent these variants may affect clinical decision making remains uncertain. Here, we evaluate 48 glioblastomas submitted for testing using the JAX ActionSeq™ Next-generation sequencing (NGS) panel. We identified 131 clinically significant variants (Tier I and II) across 30 of the 212 genes (14%). TP53, EGFR, PTEN, IDH1 were the most commonly mutated genes; EGFR, CDK4 amplifications, and CDKN2A deletion were the most frequently detected copy-number alterations. CDK4/6 and PI3K inhibitors were among the most commonly reported drug class with FDA approved therapies and investigational therapies, which is consistent with the frequencies of these genes in our cohort. Overall, our study established the molecular profiles of glioblastoma based on the 2017 joint consensus guidelines by AMP/ASCO/CAP and provides the potential implications for targeted therapeutic options currently available.